Spotted Lanternfly Lycorma delicatula (White) (Hemiptera: Fulgoridae) - Taryn B. Griffith; Jennifer L. Gillett-Kaufman (EDIS)
Originating from northern China, the spotted lanternfly, Lycorma delicatula (White), is a serious pest due to their high reproductive capacity and large host range. Spotted lanternfly is the approved ESA common name, however these insects are also referred to as the spot clothing wax cicada, or the spotted wax cicada.